(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Distance learning courses in this form introduce students to the essence of innovations in the field of law, introduce the latest achievements in the field, improve professional skills, develop skills to overcome systemic shortcomings, and constantly improve the level of training during their careers, timely theoretical and practical can serve to ensure the effectiveness of increasing professional competence through the application of knowledge, skills and competencies in practice.